How to bee - MacDibble, Bren. (Toronto: Groundwood Books, 2020)
Peony lives with her sister, Magnolia, and her grandfather on a fruit farm outside the city. All Peony really wants is to be a bee. Even though she is only nine ― and bees must be ten ― Peony already knows all there is to know about being a bee and she is determined to achieve her dream. Life on the farm is a scrabble, but there is enough to eat and a place to sleep, and there is love. Then Peony’s mother arrives to take her away from everything she has ever known. Peony is taken to the city to work for a wealthy family. Will Peony’s grit and quick thinking be enough to keep her safe? How to Bee is a beautiful and fierce novel for younger readers, and the voice of Peony will stay with you long after you read the last page.